Prognostic Role of Neutrophil to Lymphocyte Ratio in COVID-19 Patients: Still Valid in Patients That Had Started Therapy? - Gelzo, Monica; Cacciapuoti, Sara; Pinchera, Biagio; De Rosa, Annunziata; Cernera, Gustavo; Scialò, Filippo; Mormile, Mauro; Fabbrocini, Gabriella; Parrella, Roberto; Gentile, Ivan; Castaldo, Giuseppe (Frontiers in Public Health, 2021)
COVID-19 may appear with a widely heterogeneous clinical expression. Thus, predictive markers of the outcome/progression are of paramount relevance. The neutrophil/lymphocyte ratio (NLR) has been suggested as a good predictive marker of disease severity and mortality. Accordingly, we found that NLR significantly increased in parallel with the WHO severity stage in COVID-19 patients during the Ist wave (March-May 2020; n = 49), due to the significant reduction of lymphocyte and the significant increase of neutrophil in severe COVID-19 patients. While, we did not observe significant differences of NLR between the WHO severity stage among COVID-19 patients of the IInd wave (September 2020-April 2021; n = 242). In these patients, the number of lymphocytes and neutrophils did not change significantly between patients of different severity subgroups. This difference likely depends on the steroids therapy that the patients of the IInd wave performed before hospitalization while most patients of the Ist wave were hospitalized soon after diagnosis. This is also confirmed by serum interleukin (IL)-6 and myeloperoxidase (MPO) that gradually increased with the disease stage in patients of the Ist wave, while such biomarkers (whose production is inhibited by steroids) did not show differences among patients of the IInd wave in different stages. Thus, the NLR could be tested at diagnosis in naïve patients before starting therapies.